Research at the Department of Medical Informatics, Statistics and Documentation of the University of Graz - Gell, G.; Errath, M.; Simonic, K.-M. (Yearbook of Medical Informatics, 2000)
The Department of Medical Informatics, Statistics and Documentation of the University of Graz has a double responsibility: research in medical informatics, and implementation and operation of information systems in the hospital. Research is therefore application oriented with emphasis on departmental information systems, image management, and information integration. Other topics include analysis of the preconditions for the acceptance and successful use of information systems in medicine, and the ethics and professional responsibility of medical informatics.
Keywords: Medical Informatics; Information Systems; PACS; Ethics